Case Report: Kawasaki Shock Syndrome With Polycyclic Eruption: A Peculiar Brain Imaging - Masiello, Enrico; Buonsenso, Danilo; Lazzareschi, Ilaria; Gatto, Antonio; Piastra, Marco; Chiaretti, Antonio; Valentini, Piero (Frontiers in Pediatrics, 2021)
Kawasaki disease (KD) is a childhood vasculitis of unknown etiology. The present study describes a case of KD shock syndrome that occurred in an infant (age, 16 months) following 7 days of high fever and persistent rash characterized by target-like and purpuric skin lesions. The child developed neurological manifestations such as altered consciousness and irritability. Consequently, brain magnetic resonance imaging (MRI) was performed, revealing an inflammatory involvement of the anterior perforated substance and the hypothalamus. Cerebral involvement on brain MRI is rarely described in KD but when reported is characterized mostly by cerebral vasculitis. We illustrate for the first time in KD an inflammation in the brain not related to vasculitis, reporting peculiar neuroradiological findings. This last aspect has fascinated us in light of recent evidence about the immunological spectrum of Multisystem Inflammatory Syndrome in Children (MIS-C) and Kawasaki-like syndrome in the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) outbreak.